2020
DOI: 10.3390/ani10030473
|View full text |Cite
|
Sign up to set email alerts
|

Spirulina platensis Reduced Oxidative Damage Induced by Chlorpyrifos Toxicity in Nile Tilapia (Oreochromis niloticus)

Abstract: Due to the numerous pharmacological impacts of Spirulina platensis (SP), the effects of SP on the oxidative status of Nile tilapia farmed under chlorpyrifos (CPF) ambient toxicity were considered in this study. Fish (60 ± 6.1 g) was randomly stocked in five groups where the SP free diet was fed to the control group while the second one was fed 1% SP without CPF exposure. Additionally, CPF (15 μg/L) was added in water and fish were fed with SP at 0, 0.5, and 1% (third, fourth, and fifth groups, respectively). S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(23 citation statements)
references
References 51 publications
(66 reference statements)
1
22
0
Order By: Relevance
“…Atli and Canli [ 43 ] reported similar oxidative stress following exposure of Nile tilapia to acute and chronic metal toxicity. Parallel to our findings, it was found that SP can mitigate the oxidative stress markers induced after exposure of Nile tilapia to chlorpyrifos [ 26 ], arsenic toxicity [ 19 ], and sodium sulphate toxicity [ 5 ].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Atli and Canli [ 43 ] reported similar oxidative stress following exposure of Nile tilapia to acute and chronic metal toxicity. Parallel to our findings, it was found that SP can mitigate the oxidative stress markers induced after exposure of Nile tilapia to chlorpyrifos [ 26 ], arsenic toxicity [ 19 ], and sodium sulphate toxicity [ 5 ].…”
Section: Discussionsupporting
confidence: 83%
“…The final concentration of 5.8 mg/L was selected based on the previous study by Awed et al [ 5 ]. The experimental groups were named as following: G1: control group fed the basal diet only; G2 (SS): fed the basal diet and intoxicated with waterborne SS 5.8 mg/L [ 5 ]; G3 (SP): fed a diet supplemented with 1% SP [ 26 ]; and G4: fed a diet supplemented with 1% SP and intoxicated with waterborne SS 5.8 mg/L. …”
Section: Methodsmentioning
confidence: 99%
“…There are several natural feed additives were reported to reduce the CPF‐induced toxicity in fish such as ascorbic acid (Tripathi & Shasmal, 2010), propolis (Yonar et al . , 2012), lycopene (Ural, 2013), curcumin (Yonar, 2018), seeds and leaves of Moringa oleifera (Ibrahim et al, 2019), Spirulina platensis (Abdel‐Daim et al, 2020) and menthol essential oil (Dawood et al, 2020a).…”
Section: The Role Of Lycopene In Reducing the Impacts Of Aquatic Envimentioning
confidence: 99%
“…The lower liver glycogen (Table 2) and muscle glycogen values (Table 2) ( p < 0.05) in treatment C compared to controls, reinforced the increase in protein sparing effect so that oxidative deamination was reduced (Subramanian, 2013; Wardani et al, 2020a). Reduced oxidative deamination would cause a decrease in the value of reactive oxygen species (ROS) (Andersen et al, 2016), free radicals (Lupatsch et al, 2010; Zupa et al, 2015), MDA (Abdel‐Daim et al, 2020; Wardani et al, 2020a, 2020b) and plasma cortisol (Schrama et al, 2018) as stress indicators. In this study, fish fed with treatment C showed lower MDA (Table 2), cortisol and glucose values ( p < 0.05), respectively, at 30.26%, 7.57% and 15.89% compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon will increase protein retained (Schrama et al, 2018; Wardani et al, 2020a, 2020b) and improve the feed efficiency (Skov et al, 2017; Wardani et al, 2020a, 2020b), as well as reducing the ammonia excretion and heat production during the metabolic process (Andersen et al, 2016; Lazzari & Baldisserotto, 2008), and increasing immunity and fish health status. Moreover, intensive fish culture and toxin in the water (Abdel‐Daim et al, 2019, 2020) will increase death potency on the cultured fish. This begins with the stress that comes from the environment (Lazzari & Baldisserotto, 2008) and also the presence of physiological and metabolism stresses (Andersen et al, 2016) that affect lower immune status.…”
Section: Introductionmentioning
confidence: 99%